2017
DOI: 10.7726/ajhmt.2017.1003
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection in a Square Cavity Containing a Nanofluid and a Partially-heated Square Block at the Centre

Abstract: This work focuses on the numerical study of natural convection fluid flow and heat transfer of (Cu, Al2O3 and TiO2)-water nanofluids in the annuli of two partially-heated square ducts. The left and right vertical walls of the outer duct have constant but different temperatures Th and Tc respectively, while the inner duct is maintained at the same and opposite temperatures. The ducts top and bottom walls are kept insulated. The governing equations are solved numerically using the finite-volume method. The SIMPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The reader can find very intense information about the nanofluid in many review papers like Sajid and Ali [5], Kamel et al [6] and Pordanjani et al [7]. On the other side, buoyancy-driven convection, usually termed the natural convection in enclosures loaded with a nanofluid, is a very interesting phenomenon investigated by many researchers [8][9][10][11][12]. Of course, the major reason behind this attention is due to its very wide applications in many engineering fields.…”
Section: Introductionmentioning
confidence: 99%
“…The reader can find very intense information about the nanofluid in many review papers like Sajid and Ali [5], Kamel et al [6] and Pordanjani et al [7]. On the other side, buoyancy-driven convection, usually termed the natural convection in enclosures loaded with a nanofluid, is a very interesting phenomenon investigated by many researchers [8][9][10][11][12]. Of course, the major reason behind this attention is due to its very wide applications in many engineering fields.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies [8][9][10][11][12][13] have shown the effect of increasing the concentration of nanoparticles on improving heat transfer. A number of researchers studied magnetohydrodynamics (MHD).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal coupling between exothermic and endothermic reactions can be enhanced in a number of ways. One strategy might be to use "nanofluids" (Bouchta et al, 2017). Nanofluids are made up of small nanosized particles suspended in a base fluid (Xuan and Li, 2000).…”
Section: Introductionmentioning
confidence: 99%